Heart of Lymphoma: Primary Mediastinal Large B-Cell Lymphoma with Endomyocardial Involvement. (1st October 2013) - Rogowitz, Elisa; Babiker, Hani M.; Krishnadasan, Ravitharan; Jokerst, Clint; Miller, Thomas P.; Bookman, Michael
Abstract : Primary mediastinal B-cell lymphoma (PMBCL) is an uncommon aggressive subset of diffuse large B-cell lymphomas. Although PMBCL frequently spreads locally from the thymus into the pleura or pericardium, it rarely invades directly through the heart. Herein, we report a case of a young Mexican female diagnosed with PMBCL with clear infiltration of lymphoma through the cardiac wall and into the right atrium and tricuspid valve leading to tricuspid regurgitation. This was demonstrated by cardiac MRI and transthoracic echocardiogram. In addition, cardiac MRI and CT scan of the chest revealed the large mediastinal mass completely surrounding and eroding into the superior vena cava (SVC) wall causing a collar of stokes. The cardiac and SVC infiltration created a significant therapeutic challenge as lymphomas are very responsive to chemotherapy, and treatment could potentially lead to vascular wall rupture and hemorrhage. Despite the lack of conclusive data on chemotherapy-induced hemodynamic compromise in such scenarios, her progressive severe SVC syndrome and respiratory distress necessitated urgent intervention. In addition to the unique presentation of this rare lymphoma, our case report highlights the safety of R-CHOP treatment.